Clinical Characteristics and Outcomes of COVID-19 in Children in Northern Iran - Leila Shahbaznejad; Hamed Rouhanizadeh; Mohammad Reza Navaeifar; Fatemeh Hosseinzadeh; Faeze Sadat Movahedi; Mohammad Sadegh Rezai (International Journal of Pediatrics)
Objective. Since December 2019, the coronavirus disease 2019 (COVID-19) has been spread rapidly all over the world, infecting all age groups with this novel virus. In this manuscript, we report characteristics of children with COVID-19 in Mazandaran province, northern Iran. Method. From 12 February to 28 July 2020, medical records of 100 children diagnosed with COVID-19 admitted to the hospitals of Mazandaran province were collected. Patients’ age, gender, clinical symptoms, and signs, in addition to therapeutic management and outcomes, were reported. Results. 57 (57%) boys and 43 girls with the mean age of 104.63±79.14 months were evaluated. 20 patients (20%) were transferred to the PICU (pediatric intensive care unit), and 13 children experienced a severe form of the disease, pediatric inflammatory multisystem syndrome (PIMS). The mean duration of hospitalization was 5.3±4.7 days. Fever (81%), respiratory (79%), gastrointestinal (47%), and neurologic complaints (29%) were experienced by the patients in addition to skin rash (14%). Sixty-two patients needed supplemental oxygen, and 6 of them underwent endotracheal intubation. Leukopenia was reported in 7, anemia in 24, and thrombocytopenia in 12 patients. 4 patients with underlying diseases including chronic renal failure, Down syndrome with cerebral palsy, and morbid obesity died. Conclusion. COVID-19 can cause symptoms in children in two stages. In the first week, upper and lower respiratory symptoms can occur which has lower severity and prevalence compared to adults. But after 2-3 weeks following infection, symptoms of MIS-C or multisystem involvement can occur and COVID-19 should be considered. The most common indication for admission is fever, rash, and respiratory problems.